Occurrence of occupational fraud in family businesses: A Pitch - Sneha Raut (Contabilitate şi Informatică de Gestiune, 2019)
Idea generation is easy but getting a refined and organized form for that idea is a complex process. This letter outlines the utilization of Faff (2018) pitching research framework for developing a personal original pitch. The pitching research template is intriguing as it helps young researchers like myself in determining the core components of their research topic. This “Pitching Research Letter” features my personal thoughts on pitching research and the application of the pitching template to develop my personal pitch on “Occupational Fraud in Family Businesses” using the Fraud Triangle.